Improving Students' Creativity In Fine Arts Works Using The Project Based Learning Model In Grade Ii Of SD Negeri 6 Sokong - Febrianto, Yogi; Habiburrahma, Lalu; Eliyana, Eliyana (Lembaga Penelitian dan Pendidikan Mandala, 2025)
This study aims to determine the level of student creativity in collage visual art through the use of the Project Based Learning model in Class II of SD Negeri 6 Sokong for the 2024/2025 academic year. The background of this research is the low level of student creativity in art learning, as indicated by a lack of confidence in expressing ideas, limited variety in artworks, and minimal active participation in the creative process.The research employed a qualitative approach using the Classroom Action Research (CAR) method based on the Kemmis and McTaggart model, which consists of planning, action, observation, and reflection stages. The research subjects were 15 second-grade students of SD Negeri 6 Sokong. Data were collected through observation, documentation, and interviews. The instruments used included student activity observation sheets and student creativity assessment sheets.The results of the study showed that the application of the Project Based Learning model was effective in enhancing students' creativity in visual art. This was evidenced by an increase in student participation in planning and completing projects, greater confidence in expressing ideas, as well as improved quality and diversity in the students' artworks. The learning process became more meaningful as students were actively engaged, worked collaboratively, and completed real-world projects that aligned with their interests and abilities.Thus, the Project Based Learning model can be considered an effective alternative in art education to develop students’ creative potential from an early age, especially in the field of collage visual art.